Effectieve loopbaanoriëntatie en loopbaanbegeleiding (LOB) in het vmbo een overzichtsstudie van nationale en internationale literatuur - Korpershoek, Hanke (Kohnstamm Instituut, 2022)
This literature study examines which attention to CEG can be effective for pupils, with where possible also specific attention to 'what works' for young people from families with a disability. migration background, so that evidence-informed decisions about the implementation of LOB could be. We base ourselves mainly on (quasi-)experimental research in which, for example, pre- and post-measurements and partly also control groups are used to change the effectiveness of an intervention from program to program.